The peleja for public education in the context of Pandemic: reaching and extending plots - Rosilene Lagares; Leonardo Victor dos Santos; Meire Lúcia Andrade da Silva; Italo Bruno Paiva Gonçalves (Universidade Federal do Norte do Tocantins, 2020)
We question how the outcome of the pandemic of the new corona virus has been for public education in the country and in Tocantins, with education as a field of struggles with its actors imposing their political and arbitrary cultural options and their legitimate categories of perception and appreciation . In general, it seeks to discuss how this situation has influenced public education, as well as, from then on, to think about open possibilities for this education. It is based on bibliographic, documentary and hypertext analyzes. The situation rekindles the discussion about the non-priority of education by the State and reveals that the link for its destruction is thin and fragile. In a critical perspective, the conjuncture presents possibilities, implying the organization, articulation and mobilization of a broad political struggle in defense of public education in the country.